Loss sharing in central clearinghouses: Winners and losers - Christian Kubitza; Loriana Pelizzon; Mila Getmansky (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
Central clearing counterparties (CCPs) were created to reduce default losses for market participants in derivatives markets. We show that not all market participants benefit, and some are worse off. Loss sharing rules and their interaction with market network structure affect who are winners and losers. The loss sharing rule most widely used by CCPs is based on net risk. We develop a simple model which shows that this rule largely benefits market participants with flat portfolios but not participants with directional portfolios or those located in the periphery of the network. This result is consistent with the reluctance of (peripheral) end-users to voluntarily clear in practice. We investigate how to offset cross-sectional differences in loss sharing benefits, and highlight alternative loss sharing rules and centralized trading as potential remedies.
Keywords: G18; G23; G28; G12; 330; Central Clearing; Counterparty Risk; Loss Sharing; OTC markets; Derivatives